Retro-aortic left renal vein as an uncommon cause of left sided varicocele and haematuria - Norhasiza, Mat Jusoh; Hun, Cheah Wai; Yasrul Izad, Abu Bakar (Penerbit Universiti Sultan Zainal Abidin, 2020)
Retro-aortic left renal vein [RLRV] is a congenital anomaly characterised by a left renal vein passing posterior to abdominal aorta. It has been suggested that RLRV may cause varicocele and haematuria. The urological symptoms are probably due to the increased pressure in the left renal vein secondary to posterior nutcracker phenomenon. The diagnosis of RLRV is usually radiological. We report a case of a 53-year old man who presented with left scrotal swelling which was then confirmed to be varicocele by Doppler ultrasound. Two months later, the patient had microscopic haematuria and computed tomography [CT] abdomen and pelvis scan was done. CT showed presence of RLRV.